Clinical anatomy a core text with self-assessment - Monkhouse, Stanley (Master medicine, 2007)
This title is directed primarily towards health care professionals outside of the United States. It is a short, highly readable and well illustrated book on anatomy, approached from the point of view of what medical students need to know in order to understand the clinical work they will eventually be doing. Includes a great variety of self-assessment, to reinforce the messages and to test understanding - and to help students prepare for exams. Concise synoptic (not telegraphic text). Appropriate self-assessment material. Only covers core, so student knows the whole boo.